Analisis Pengendalian Bahaya dengan Metode Job Safety Analysis dan Fault Tree Analysis pada Pembuatan Rangka Custom Motor (Studi Kasus Dibengkel Sumber Maju Motor) - Aditya, Ivanka; Rusmalah, Rusmalah; Ahmad, Wakhit; Alfatiyah, Rini (Universitas Pamulang, 2022)
Sumber Maju Motor is a service workshop for making custom motorcycle frames that modify the original form of a manufacturer's motorcycle frame to suit the wishes of the motorcycle owner. In the Sumber Maju Motor Workshop, there are various kinds of problems that occur. One of them is the problem that occurs several times, namely work accidents when working on the manufacture of motorcycle parts due to the K3 program not yet running. The research entitled ANALYSIS OF HAZARD CONTROL USING JOB SAFETY ANALYSIS AND FAULT TREE ANALYSIS METHODS INCUSTOM MOTOR FRAME MANUFACTURING (Case Study at Sumber Maju Motor Workshop). This study aims to identify the causes of work accidents that occur and apply the K3 system during the process of working on a custom motorcycle frame with the Job Safety Analysis (JSA) method in an effort to control hazards or risks arising from the work carried out and Fault Tree Analysis (FTA) to find the source of the most basic cause of an accident at work. Based on the results of the JSA, control of work accidents by procuring PPE for its employees in order to support occupational safety and health when doing work for each employee and the discipline of each employee in prioritizing work safety. While the results of the FTA analysis on the risk of being scratched by sharp edges, shortness of breath, and hearing loss are caused by various factors including equipment factors, work environment factors, and human factors that can cause work accidents.